2017
DOI: 10.4103/atm.atm_298_16
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial ultrasound plus fluoroscopy-guided biopsy compared to fluoroscopy-guided transbronchial biopsy for obtaining samples of peripheral pulmonary lesions: A systematic review and meta-analysis

Abstract: BACKGROUND:We report a meta-analysis of recent studies comparing the diagnostic yields of endobronchial ultrasonography plus fluoroscopically-guided transbronchial biopsy (EBUS + TBB) with that of conventional fluoroscopically-guided TBB for peripheral pulmonary lesions (PPLs).METHODS:We searched Medline, the Cochrane Library, PubMed, and Google Scholar through 31 March 2013 using the keywords: lung neoplasm, pulmonary lesions, diagnosis, endobronchial ultrasound, fluoroscopy, and fluoroscopic.RESULTS:Four stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Finally, auxiliary bronchoscopic procedures, such as fluoroscopy or a guide sheath, were not conducted on our study subjects. Since adding these modalities to rEBUS-guided TBB may help achieve a rather favorable diagnostic yield in PPLs, [ 17 , 18 ] it is uncertain whether our findings remain valid when ancillary tools are coupled to rEBUS-guided procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, auxiliary bronchoscopic procedures, such as fluoroscopy or a guide sheath, were not conducted on our study subjects. Since adding these modalities to rEBUS-guided TBB may help achieve a rather favorable diagnostic yield in PPLs, [ 17 , 18 ] it is uncertain whether our findings remain valid when ancillary tools are coupled to rEBUS-guided procedures.…”
Section: Discussionmentioning
confidence: 99%
“…H erth et al . [ 5 ] first described the use of EBUS to guide transbronchial biopsy (TBB) of PPLs in 2002, and numerous studies since then have shown a superior diagnostic yield of PPLs using TBB under EBUS guidance, as compared to conventional bronchoscopy [ 6 9 ]. A notable methodological limitation inherent to EBUS is that it does not provide real-time images for TBB procedures; thus, the biopsy forceps may not always be advanced into the target bronchus from which the EBUS image has been obtained.…”
Section: Introductionmentioning
confidence: 99%